Perbandingan Bentuk Kelembagaan Program Penjaminan Polis Asuransi Antara Indonesia dengan United Kingdom dan Jepang - Novianty, Annisa; Simanjuntak, Kornelius (Universitas Batanghari Jambi, 2024)
Insurance company defaults in Indonesia have a negative impact on policyholders. Suing the company for bankruptcy is the last resort for policyholders to obtain compensation from the company's assets, but the enforcement of court judgements is difficult due to obstacles such as abuse of receivership powers. Policyholders' rights are often violated as they do not receive insurance claim payments. Law No. 40 of 2014 requires insurance companies to participate in the Policy Guarantee Programme and establish a Policy Guarantee Agency within two years. However, such an institution has not yet been established in Indonesia. This research compares the Policy Guarantee Programmes in the UK and Japan to show the importance of establishing a similar institution to protect the rights of policyholders. This research uses normative research with a comparative approach and legislation. By studying the sustainability of the Financial Services Compensation Scheme in the UK and the Life Insurance Policyholders Protection Corporation in Japan, the research recommends that the Indonesian government promptly establishes a Policy Guarantee Corporation, either as an independent institution or in conjunction with the existing Deposit Insurance Corporation for the banking sector.